Microsoft Cambridge at TREC-9: Filtering track - Robertson, Stephen; Walker, S. (The Ninth Text REtrieval Conference (TREC-9), 2001)
Apart from a short description of our Query Track countribution, this report is concerned with the Adaptive Filtering track only. There is a separate report in this volume [1] on the Microsoft Research Cambridge participation in QA track. A number of runs were submitted for the Adaptive Filtering track, on all tasks (adaptive filtering, batch filtering and routing; three separate query sets; two evaluation measures). The filtering system is somewhat more advanced than the one used for TREC-8, and includes query modification and a more highly developed scheme for threshold adaption. A number of diagnostic runs are also reported here.